2014
DOI: 10.1177/2047487314526071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on different quality of life dimensions in heart failure with preserved ejection fraction: the Ex-DHF-P trial

Abstract: In patients with HFpEF, exercise training improved emotional status, physical and social dimensions of QoL as well as symptoms of depression from pre to post test. Physical dimensions of QoL and general health perception also improved significantly with exercise in comparison to usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 44 publications
5
64
0
14
Order By: Relevance
“…Dostępne są dowody wskazujące, że u pacjentów z HFpEF trening fizyczny przynosi wiele korzyści, w tym wpły-wa na poprawę wydolności wysiłkowej, określaną obiektywnie za pomocą oceny pochłaniania tlenu na szczycie wysiłku, poprawę jakości życia i funkcję rozkurczową ocenianą w badaniu echokardiograficznym [321,620,621,634].…”
Section: Trening Wysiłkowyunclassified
“…Dostępne są dowody wskazujące, że u pacjentów z HFpEF trening fizyczny przynosi wiele korzyści, w tym wpły-wa na poprawę wydolności wysiłkowej, określaną obiektywnie za pomocą oceny pochłaniania tlenu na szczycie wysiłku, poprawę jakości życia i funkcję rozkurczową ocenianą w badaniu echokardiograficznym [321,620,621,634].…”
Section: Trening Wysiłkowyunclassified
“…Regular physical activity and structured exercise training (ET) are a cornerstone of non‐pharmacological management in HF patients 4, 5. ET was found to be effective in improving cardiorespiratory fitness6, 7 and dimensions of quality of life in patients with HFpEF 8. Strikingly, ET as a mean of cardiovascular rehabilitation has also been associated to improved left ventricular diastolic function in patients with reduced6 and preserved7 ejection fraction.…”
Section: Introductionmentioning
confidence: 99%
“…These positive findings are validated by other studies that reported the impact of exercise training on psychological effects among participants with heart failure. 18,36,37 Before our analysis, several competing theories could be offered to explain the lack of effect of exercise training on psychological outcomes. First, exercise may not be a powerful enough intervention to alter the emotional response of participants, many of whom have lived with a chronic, progressive syndrome for years.…”
Section: Discussionmentioning
confidence: 99%